'Empowering our people' to address depression, violence, and sexual risk among Native Americans with recent binge alcohol use. Issue 3 (3rd April 2022) - Tingey, Lauren; Chambers, Rachel; Littlepage, Shea; Slimp, Anna; Lee, Angelita; Lee, Shauntel; Melgar, Laura; O'Keefe, Victoria; Craig, Mariddie; Gaydos, Charlotte; Rompalo, Anne
ABSTRACT: Background: This study was launched in response to an American Indian (AI) community's concern regarding the comorbid occurrence of substance use, poor mental health, and other risk factors on sexual health. The purpose of this manuscript was to assess the relationship between alcohol use, violence, depression and STI/HIV risk behaviors on the frequency of unprotected sex acts and number of sexual partners among AI adults. Methods: Specifically, this analysis examines sociodemographic characteristics, experience of sexual and physical violence, binge drinking, depression, and sexual risk taking among n = 281 AI adults ages 18–55. Regression models examine associations between the aforementioned risk factors, number of sex partners and number of unprotected sex acts, by depression status and sex, among participants. Results: Frequent binge drinking predicted frequency of unprotected sex for both males and females; ever experiencing physical violence was a powerful predictor of unprotected sex for females, but not males. Ever experiencing physical violence strongly predicted having multiple sexual partners for females but was related to decreased number of sexual partners for males. Females ever experiencing sexual violence had more sexual partners; this was not observed for males. Binge drinking predicted frequency of unprotected sex acts, regardless of depression status. Discussion: Interventions for AI adults seeking to reduce sexual health risk should reflect past violence victimization in sexual decision making, primarily among women. The significant role of binge alcohol use for modifying sexual decisions should be of prime focus and interventions should be personalized to address individuals' own alcohol use patterns. Additional research should explore how binge alcohol use moderates the relationship between depression and sexual risk.